If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(4 + -4m) + 3(1 + 4m) = 6 + -2m + m + -5 (4 * 2 + -4m * 2) + 3(1 + 4m) = 6 + -2m + m + -5 (8 + -8m) + 3(1 + 4m) = 6 + -2m + m + -5 8 + -8m + (1 * 3 + 4m * 3) = 6 + -2m + m + -5 8 + -8m + (3 + 12m) = 6 + -2m + m + -5 Reorder the terms: 8 + 3 + -8m + 12m = 6 + -2m + m + -5 Combine like terms: 8 + 3 = 11 11 + -8m + 12m = 6 + -2m + m + -5 Combine like terms: -8m + 12m = 4m 11 + 4m = 6 + -2m + m + -5 Reorder the terms: 11 + 4m = 6 + -5 + -2m + m Combine like terms: 6 + -5 = 1 11 + 4m = 1 + -2m + m Combine like terms: -2m + m = -1m 11 + 4m = 1 + -1m Solving 11 + 4m = 1 + -1m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add 'm' to each side of the equation. 11 + 4m + m = 1 + -1m + m Combine like terms: 4m + m = 5m 11 + 5m = 1 + -1m + m Combine like terms: -1m + m = 0 11 + 5m = 1 + 0 11 + 5m = 1 Add '-11' to each side of the equation. 11 + -11 + 5m = 1 + -11 Combine like terms: 11 + -11 = 0 0 + 5m = 1 + -11 5m = 1 + -11 Combine like terms: 1 + -11 = -10 5m = -10 Divide each side by '5'. m = -2 Simplifying m = -2
| 7x-2-19x= | | 5=(z/-4)-3 | | W+1=-9 | | A=4(b-c)/d | | -12+3k=3-2k | | M-(13)=37 | | 6-(g+3)=8g | | 15-x=3.5 | | 3u^3+7u^2+6u+14= | | 3(7y-9)= | | 0.65(m-11)+0.35m=-3.15 | | -2.4=-0.9u+0.5u | | 6-10n=26 | | 2/7m-17=3/14 | | 7x-8y+5x-x+2y= | | 1.4=(-x)-3(1.4) | | 5x=(3x/2) | | (5/6) | | 15x^2+25x^6y^4=0 | | 4+7r=39 | | 21/30÷4/3 | | M-6.1=9.4 | | (2x/5)-(x/6)=-7/10 | | 9+3(z-3)=2z+3 | | 1.9n-48.4=3n | | 5.2+y=7.9 | | x^2+y^2=44 | | 4(3x)-8x/2=216 | | 2x+5x=42 | | (8/7)(8/7)= | | 27+t=-31 | | -83+5x=-2x+78 |